Exploring cross-curriculum numeracy understanding and implementation in Santa Angela teachers - Romlah Tresna Dewi; Rusman Rusman (Himpunan Pengembang Kurikulum Indonesia, 2025)
Numeracy literacy is a key component in achieving the 4th Sustainable Development Goal and is part of Indonesia’s National Graduate Competency Standards, as outlined in Permendikbudristek No. 5 of 2022. However, data from the National Education Report Card over three years consistently shows that numeracy achievements lag reading literacy. Numeracy, a critical 21st-century skill, extends beyond mathematics, supporting students' ability to think critically and engage productively in a data-driven world. The Merdeka Curriculum highlights the significance of developing numeracy as a foundational competency across subjects. This study explores non-mathematics teachers' understanding and implementation of cross-curricular numeracy at Saint Angela Primary School. A mixed-methods approach was used, combining quantitative analysis of teacher responses to the questionnaire and thematic analysis of qualitative data on their views and experiences. Findings reveal that while most teachers have a solid understanding of numeracy and have attempted integration into lessons, the frequency of implementation remains low. Challenges include limited training, insufficient resources, and time constraints in lesson planning. This study underscores the need for enhanced teacher support and professional development to promote effective numeracy integration, with broader implications for curriculum design in primary education. Abstrak Literasi numerasi merupakan komponen kunci dalam pencapaian Tujuan Pembangunan Berkelanjutan (TPB) ke-4 dan menjadi bagian dari Standar Kompetensi Lulusan Nasional Indonesia sebagaimana diatur dalam Permendikbudristek No. 5 Tahun 2022. Namun, data dari Rapor Pendidikan Nasional selama tiga tahun berturut-turut menunjukkan bahwa capaian numerasi secara konsisten lebih rendah dibandingkan capaian literasi membaca. Numerasi, sebagai keterampilan penting abad ke-21, tidak hanya relevan dalam pelajaran matematika, tetapi juga mendukung kemampuan siswa untuk berpikir kritis dan berkontribusi secara produktif dalam dunia yang dipenuhi data. Kurikulum Merdeka menekankan pentingnya pengembangan numerasi sebagai kompetensi dasar lintas mata pelajaran. Penelitian ini mengeksplorasi pemahaman dan implementasi numerasi lintas kurikulum oleh guru nonmatematika di SD Santa Angela. Pendekatan metode campuran digunakan dengan analisis kuantitatif terhadap respons kuesioner guru serta analisis tematik terhadap data kualitatif terkait pandangan dan pengalaman mereka. Hasil penelitian menunjukkan bahwa meskipun sebagian besar guru memiliki pemahaman yang baik tentang numerasi dan telah mencoba mengintegrasikannya dalam pembelajaran, frekuensi penerapannya masih rendah. Tantangan utama meliputi kurangnya pelatihan, keterbatasan sumber daya, dan waktu untuk perencanaan pembelajaran. Penelitian ini menekankan pentingnya dukungan tambahan dan pengembangan profesional bagi guru untuk mendorong integrasi numerasi yang efektif, serta implikasinya terhadap pengembangan kurikulum di sekolah dasar. Kata Kunci: integrasi lintas kurikulum; kurikulum Merdeka; literasi numerasi